A promising route of magnetic based materials for removal of cadmium and methylene blue from waste water - Ruthiraan, Manimaran; Abdullah, Ezzat Chan; Mubarak, N.M.; Mohamed Noor, Noraini (Elsevier, 2017)
Adsorption equilibrium is an essential measure to be controlled in attaining the maximum capacity of an adsorbent. Synthesis of magnetic biochar by using various discarded biomass possesses varied adsorbate adsorption capability. Maximising the removal percentage of the pollutant from wastewater by altering operational parameters are the very important skill to be mastered by environmentalist. In this research work, mangosteen peel derived ferric oxide magnetic biochar was pyrolysed at 800 C for 20 min via modified muffle furnace at zero oxygen environment. The factors affecting adsorption were studied for two different liquid pollutant. A comparative study was carried out for adsorption of methylene blue dye and Cd (II) ions by altering the adsorbate pH, agitation speed, and contact time and particle diffusion mechanism were investigated respectively. The removal of methylene blue dye attained maximum removal at pH of 7.0 and above, 50 min contact time and 150 rpm agitation speed. Moreover, adsorption equilibrium of Cd (II) ions reaches maximum removal percentage at the pH value of 8.0, agitation speed of 150 rpm and 60 min contact time. The thermodynamics study was performed to further understand the effect of operating temperature in determining the adsorption spontaneous of adsorption medium. The experimental analysis reveals that the produced magnetic biochar is viable for adsorption of both heavy metal ions and organic pollutant at optimised condition